2011
DOI: 10.3892/ijo.2011.1144
|View full text |Cite
|
Sign up to set email alerts
|

Upregulation of NKG2D ligands and enhanced natural killer cell cytotoxicity by hydralazine and valproate

Abstract: Abstract. Natural killer cells play a role in the immune antitumor response by recognizing and eliminating tumor cells through the engagement of NKG2D receptors with their ligands on target cells. This work aimed to investigate whether epigenetic drugs are able to increase MICA and MICB expression as well as NK cell cytotoxicity. Prostate, colon, breast and cervical cancer cell lines were analyzed for the expression of MICA and MICB at the mRNA and protein levels by RT-PCR, Western blot, flow cytometry and ELI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 37 publications
1
19
1
Order By: Relevance
“…Of note, the METADRUG™ program also indicated that hydralazine could act positively in the regulation of H3K4 methylation which was not observed in our study, however, recent data from our group indicate that in several cancer cell lines treatment with hydralazine and valproic acid led to over-expression of MIC A and MIC B ligands which was accompanied by an increase in H3K4 methylation at these gene promoters suggesting that hydralazine could have this effect upon this histone mark [54].…”
Section: Discussioncontrasting
confidence: 77%
“…Of note, the METADRUG™ program also indicated that hydralazine could act positively in the regulation of H3K4 methylation which was not observed in our study, however, recent data from our group indicate that in several cancer cell lines treatment with hydralazine and valproic acid led to over-expression of MIC A and MIC B ligands which was accompanied by an increase in H3K4 methylation at these gene promoters suggesting that hydralazine could have this effect upon this histone mark [54].…”
Section: Discussioncontrasting
confidence: 77%
“…Both miR-302c and miR-520c have the same ‘seed' sequence and have the same targets (Figure 4A). Of all the hypothetical targets of miR-302c and miR-520c, MICA, MICB, and ULBP2 were of the most interest because these are NKG2D ligands reported to be associated with NK cell-mediated cytotoxicity (Chavez-Blanco et al , 2011; Fernandez-Messina et al , 2012; Hilpert et al , 2012). To further identify whether MICA, MICB, and ULBP2 responded to miR-302c and miR-520c through direct 3′-UTR interactions, we cloned the wt 3′-UTRs of the putative miR-302c and miR-520c targets (MICA-wt, MICB-wt, and ULBP2-wt) and mutated sequences (MICA-mt1+2, MICB-mt1+2, and ULBP2-mut) individually into a reporter plasmid (pSi-CHECK2) downstream of the Renilla luciferase gene (Figure 4A, P <0.01).…”
Section: Resultsmentioning
confidence: 99%
“…For example, the administration of hydralazine and valproate can increase the expression of MICA and MICB ligands in the CaSki cervical cancer cell line and reduce their shedding to the supernatant, allowing NK attack; while cells without hydralazine and valproate are not susceptible to NK attack [57] (Table 1). …”
Section: Natural Killer Cells: An Important Barrier Against Cells mentioning
confidence: 99%